2014
DOI: 10.1007/s11633-014-0825-2
|View full text |Cite
|
Sign up to set email alerts
|

A wavelet neural network based non-linear model predictive controller for a multi-variable coupled tank system

Abstract: Abstract:In this paper, a novel real time non-linear model predictive controller (NMPC) for a multi-variable coupled tank system (CTS) is designed. CTSs are highly non-linear and can be found in many industrial process applications. The involvement of multi-input multi-output (MIMO) system makes the design of an effective controller a challenging task. MIMO systems have inherent couplings, interactions in-between the process input-output variables and generally have an complex internal structure. The aim of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Finally, let us mention some investigations completed in [35], where a new NMPCnonlinear model-predictive controller, working in RT, to regulate a multi-degrees-offreedom CTS, is elaborated. The researchers applied a DAQ device NI-6009 coupled with LabVIEW to acquire streams of data (a multi-input control of levels in both tanks) from sensors in RT.…”
Section: Labview Virtual Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, let us mention some investigations completed in [35], where a new NMPCnonlinear model-predictive controller, working in RT, to regulate a multi-degrees-offreedom CTS, is elaborated. The researchers applied a DAQ device NI-6009 coupled with LabVIEW to acquire streams of data (a multi-input control of levels in both tanks) from sensors in RT.…”
Section: Labview Virtual Instrumentsmentioning
confidence: 99%
“…A coupled or cascaded two-tank dynamical system, which is investigated in [17,[66][67][68][69] (state-space approach, PI, PID), [11,12,23,25,30,36] (transfer function approach), [35,70,71] (FL, PSO, NN), [72] (autoregressive model), [73] (multidimensional regularization), [74] (model-predictive control of a geometry-varying conical tank), and [75,76] (SMC); 3.…”
Section: Mathematical Modelingmentioning
confidence: 99%
“…Consequently, wavelet neural networks have been widely used in identification and predictive control of nonlinear systems. [38][39][40][41][42] In this study, we use a wavelet neural network with feedforward component and model predictive controller for online nonlinear system identification and control. The feedforward component drastically reduces the number of hidden layer nodes and, consequently, reduces the training time of the WNN while maintaining satisfactory identification performance.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang and Benveniste 37 proposed WNNs as an alternative to neural networks for system identification and demonstrated that WNNs typically have fewer nodes than other artificial neural networks. Consequently, wavelet neural networks have been widely used in identification and predictive control of nonlinear systems 38‐42 . In this study, we use a wavelet neural network with feedforward component and model predictive controller for online nonlinear system identification and control.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, both tank groups are cross coupled. Many of the methods used for systems in a SISO structure cannot be used effectively to the MIMO systems due to the coupled structure of them . Therefore, the SMC method alone is not sufficient for this experimental study.…”
Section: Introductionmentioning
confidence: 99%